2020
DOI: 10.1038/s41380-020-0734-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study and multi-tissue replication of individuals with alcohol use disorder: evidence for abnormal glucocorticoid signaling pathway gene regulation

Abstract: Alcohol use disorder (AUD) is a chronic debilitating disorder with limited treatment options and poorly defined pathophysiology. There are substantial genetic and epigenetic components; however, the underlying mechanisms contributing to AUD remain largely unknown. We conducted the largest DNA methylation epigenome-wide association study (EWAS) analyses currently available for AUD (total N = 625) and employed a top hit replication (N = 4798) using a cross-tissue/crossphenotypic approach with the goal of identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Genomic study on brain tissue samples from MDD and BD patients revealed increased mRNA expression of inflammatory genes in frontal region, reward related brain region ( 25 , 26 ). Furthermore, epigenome-wide association studies (EWAS) have revealed epigenetic associations between inflammatory genes like GAS5 and phenotypes such as fear conditioning and extinction in chronic alcohol drinkers ( 27 ). These studies provide a basis for the transcriptional regulation of neuroendophenotypes in mood and substance use disorders by inflammatory genes.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic study on brain tissue samples from MDD and BD patients revealed increased mRNA expression of inflammatory genes in frontal region, reward related brain region ( 25 , 26 ). Furthermore, epigenome-wide association studies (EWAS) have revealed epigenetic associations between inflammatory genes like GAS5 and phenotypes such as fear conditioning and extinction in chronic alcohol drinkers ( 27 ). These studies provide a basis for the transcriptional regulation of neuroendophenotypes in mood and substance use disorders by inflammatory genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several intronic γ-aminobutyric acid β1 (GABA β1) subunit (GABR β1)single nucleotide polymorphisms that may directly influence alcohol dependence risk have been recently identified ( 1 ). DNA methylation of growth arrest specific five gene is implicated in alcohol use ( 2 ). In addition, carriers of the rs1789891 A allele reportedly consume more alcohol and have a higher risk of relapse than individuals that are homozygous for the C allele ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…We searched major studies of alcohol consumption for all of the genes replicated in three AUD studies. 26 , 42 , 43 Heterogenous Nuclear Ribonucleoprotein A1 ( HNRNPA1 ) was significantly hypomethylated in AUD cases in three studies that included saliva, lymphocytes and blood, 29 , 44 , 45 and HNRNPA1 methylation was inversely associated with alcohol consumption in blood 42 , 46 and saliva. 26 HNRNPA1 regulates RNA processing, including transcription, translation, splicing, stability and export.…”
Section: Recent Molecular Discoveriesmentioning
confidence: 99%